Expression profiles of eNOS, iNOS and microRNA-27b in the corpus cavernosum of rats submitted to chronic alcoholism and Diabetes mellitus - Cunha,Joao Paulo da (2017)
Abstract Purpose: To evaluate the expression of endothelial and inducible NOS in addition to the miRNA-27b in the corpus cavernosum and peripheral blood of healthy rats, diabetic rats, alcoholic rats and rats with both pathologies. Methods: Forty eight Wistar rats were divided into four groups: control (C), alcoholic (A), diabetic (D) and alcoholic-diabetic (AD). Samples of the corpus cavernosum were prepared to study protein expressions of eNOS and iNOS by immunohistochemistry and expression of miRNA-27b in the corpus cavernosum and peripheral blood. Results: Immunohistochemistry for eNOS and iNOS showed an increase in cavernosal smooth muscle cells in the alcoholic, diabetic and alcoholic-diabetic groups when compared with the control group. Similarly, the mRNA levels for eNOS were increased in cavernosal smooth muscle (CSM) in the alcoholic, diabetic and alcoholic-diabetic groups and miRNA-27b were decreased in CSM in the alcoholic, diabetic and alcoholic-diabetic groups. Conclusion: The major new finding of our study was an impairment of relaxation of cavernosal smooth muscle in alcoholic, diabetic, and alcoholic-diabetic rats that involved a decrease in the nitric oxide pathway by endothelium-dependent mechanisms accompanied by a change in the corpus cavernosum contractile sensitivity.